1995
DOI: 10.1099/0022-1317-76-10-2423
|View full text |Cite
|
Sign up to set email alerts
|

Reversible nucleolar translocation of Epstein--Barr virus-encoded EBNA-5 and hsp70 proteins after exposure to heat shock or cell density congestion

Abstract: The Epstein-Barr virus (EBV)-encoded, nuclear matrix-associated EBNA-5 protein is preferentially localized within distinct nuclear blobs in EBV-immortalized lymphoblastoid cell lines. We have previously found that the same blobs also contain retinoblastoma (Rb) protein. We now show that they contain hsp70 protein as well. Both EBNA-5 and hsp70 translocate to the nucleolus under cell density congestion or after heat shock. Both proteins relocate to their original position upon the re-establishment of normal phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 11 publications
(11 reference statements)
2
56
0
Order By: Relevance
“…Immunostaining and digital image capturing was carried out as described (Szekely et al, 1996(Szekely et al, , 1997(Szekely et al, , 1998 using the anti-EBNA-3A monoclonal antibody T2.78-19.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunostaining and digital image capturing was carried out as described (Szekely et al, 1996(Szekely et al, , 1997(Szekely et al, , 1998 using the anti-EBNA-3A monoclonal antibody T2.78-19.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…EBNA-6 moreover has papilloma virus E7 like functions. EBNA-5 accumulates in the PML containing oncogenic domains (PODs) where it co-localizes with the retinoblastoma tumor suppressor protein (Szekely et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some viral proteins such as ICPO (Maul et al, 1993), the adenoviral protein E1A, E4-ORF3, and E1B (Carvalho et al, 1995;Doucas et al, 1996). Epstein-Barr nuclear protein 5 (Szekely et al, 1996), and a novel ubiquitin-speci®c protease (Everett et al, 1997) are shown to target and reorganize PODs. These studies demonstrated that after virus infection a dramatic structural change in the PODs was found, suggesting that PODs are the target of tumor virus oncoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro EBV-converted subline BL41\95 that has switched to a more immunoblastic (type III) phenotype (Torsteinsdottir et al, 1989) showed increased expression of the pNDCFs and vimentin. Most of the pNDCFs were associated with cytoplasmic filaments in these cells, as in LCLs and some type III BLs (Szekely et al, 1997).…”
Section: Increased Expression Of Pndcfs In Lmp1-transfected Blsmentioning
confidence: 99%
“…They are not expressed in phenotypically representative (type I) BL cells, or are only present at low levels, localized within the nucleus. In EBVimmortalized LCLs and in some of the LCL-like (type III) BL cell lines, the pNDCFs are expressed at a high level, preferentially associated with vimentin filaments in the cytoplasm (Szekely et al, 1997).…”
Section: Introductionmentioning
confidence: 99%